2011
DOI: 10.1007/s10236-011-0401-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiplatform observation of the surface circulation in the Gulf of Naples (Southern Tyrrhenian Sea)

Abstract: The Gulf of Naples (Southern Tyrrhenian Sea) is a highly urbanised area, where human activities and natural factors (e.g. river runoff, exchanges with adjacent basins) can strongly affect the water quality. In this work we show how surface transport can influence the distribution of passively drifting surface matter, and more in general if and how the circulation in the basin can promote the renovation of the surface layer. To this aim, we carried out a multiplatform analysis by putting together HF radar curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 43 publications
0
67
0
Order By: Relevance
“…Since the applications related to the management of the marine environment and emergencies at sea require accurate prediction of Lagrangian trajectories, several studies have assessed the effectiveness of trajectory predictions using currents derived from HFR (Menna et al, 2007;Uttieri et al, 2011;Solabarrieta et al, 2016). An example of calculation of Lagrangian trajectories using HFR data is shown in Figure 5.…”
Section: Applications Of Hfr Measurements In the Framework Of The Eurmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the applications related to the management of the marine environment and emergencies at sea require accurate prediction of Lagrangian trajectories, several studies have assessed the effectiveness of trajectory predictions using currents derived from HFR (Menna et al, 2007;Uttieri et al, 2011;Solabarrieta et al, 2016). An example of calculation of Lagrangian trajectories using HFR data is shown in Figure 5.…”
Section: Applications Of Hfr Measurements In the Framework Of The Eurmentioning
confidence: 99%
“…Using different FIGURE 5 | Example of Lagrangian application. Series of 12-h snapshots of the time evolution of 10,000 tracer particles in the Gulf of Naples, deployed along the urban littoral, dispersing over the whole Gulf and eventually reaching the opposite Sorrento peninsula in the turn of 3 days (Gulf of Naples AMRA-CoNISMa-UniParthenope HFR system; for validation of these results with satellite imagery see Uttieri et al, 2011). assimilation approaches (e.g., optimal interpolation, ensemble Kalman methods, 4DVAR) it was demonstrated that HFR data can be used to significantly improve forecasts of currents and other oceanographic variables in coastal areas. There seems to be, however, room for improvement, e.g., concerning the length of the forecast horizons.…”
Section: Applications Of Hfr Measurements In the Framework Of The Eurmentioning
confidence: 99%
See 1 more Smart Citation
“…An HF radar system has been active since 2004 over almost the entire area of the GoN and has been used in different applications in recent years (e.g. Cianelli et al, 2013;Menna et al, 2007;Uttieri et al, 2011). Most of the HF radar-based investigations focus on relatively short periods of time (from days to weeks), and only a few use radar-derived current measurements over periods of six months or longer (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Five papers in this special issue use highfrequency radar for various purposes: three of them use a combination of radar data and hydrodynamic modelling to study the spatio-temporal variability of the German Bight (Port et al 2011), the Gulf of Lions (Schaeffer et al 2011) and the Gulf of Naples (Uttieri et al 2011). Barth et al (2011) assimilate radar data into a hydrodynamical model of the German Bight, allowing for the improvement of the wind field used to force the hydrodynamical model.…”
mentioning
confidence: 99%